Sosialisasi Identifikasi Telur Konsumsi dan Telur Tetas Infertile yang Beredar di Masyarakat Melalui Media Daring - Ken Ratu Gharizah Alhuur; Andry Pratama; Endah Yuniarti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The price fluctuations of DOC (Day Old Chicken) that occurred at the beginning of the Covid-19 pandemic caused many infertile hatching eggs to be found sold freely in the community. The selling price of infertile hatching eggs (HE) is lower than consumption eggs and public ignorance about the differences between these two types of eggs makes HE eggs much sought after by the public. This is certainly a problem for producers of consumption eggs and the poultry breeding industry, because this incident is in conflict with the rules regarding the circulation of hatching eggs in the community. In addition, there is a lot of inaccurate information circulating in the community regarding HE so it is necessary to educate the public in responding to this condition. The socialization on how to identify or differentiate between consumption eggs and hatching eggs was carried out by means of discussions among lecturers, students, and community through online media. The benefits and results of this education are that participants know the rules regarding the circulation of HE in the community, participants know the correct information about HE eggs, and participants can know the characteristics of consumption eggs and HE in general one of which is based on the color of the egg shell, and participants can take a wiser attitude in the future. the day the phenomenon of HE eggs being sold in the market repeated itself. Public knowledge about egg quality increased by 33.4% through this socialization.